Low Fifth-Minute Apgar Score Analysed According to Robson Ten Group Classification at a Tertiary Hospital in Nigeria - Makinde, Olakunle; Awotundun, Benjamin O.; Osegi, Nkencho (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: Robson classification can be used to analyze and audit other indices of delivery outcome besides cesarean section (CS). The objective is to analyze low fifth-minute APGAR scores according to Robson’s classification and present deducible conclusions. STUDY DESIGN: A cross-sectional dataset of 584 neonates of parturients at the Federal Medical Centre Yenagoa (FMCY), Bayelsa State, Nigeria between July 2020 and April 2021 was analyzed. Neonates were classified by the corresponding Robson group with subgroup modification of their mothers. Data was analyzed using IBM SPSS Statistics version 25. Descriptive statistics and association between low fifth-minute APGAR Score and the Robson group are presented. The statistical significance is a p value <0.05. RESULTS: The largest contribution (29.6%) to the low fifth-minute APGAR score was from Robson group 3. Group rate was high in groups 10b (66.7%), 7a (61.1%), 10a (53.6%), 9a (50.0%), 6a (50.0%), 5.2a (33.3%) and 10c (30.3%) relative to others. Neonates of parturients in Robson groups 6a (OR - 11.00; 95% CI-1.27-95.18; p Value-0.029), 7a (OR-17.29; 95% CI-3.06-97.52; p value-0.001), 9a (OR-11.00; 95% CI-1.48-81.61; p Value-0.019), 10a (OR-12.69; 95% CI-2.49 - 64.58; p value-0.002) and 10b (OR-22.00; 95% CI-1.33 -362.92; p value-0.031) had significantly higher odds of low fifth-minute APGAR score relative to 8c with the lowest group rate. CONCLUSION: Meaningful deduction is possible with use of the Robson’s classification for audit of low APGAR Score. By this study, parturients in Robson groups 3, 5.2a, 6a, 7a, 9a, 10a, 10b, and 10c are identified for focused interventions towards improving APGAR score outcomes at FMCY.